Integration of Science and Religion at UIN Sunan Kalijaga Yogyakarta - Nanat Fatah Natsir; Erni Haryati; Hani Yuliawanti; Fahren Sepujan Nasution; Fatih Nur Afif (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
In the modern era characterized by rapid developments in science and technology, the need for the integration of knowledge and religion has become increasingly pressing. While these two elements have distinct domains, they possess the potential to complement each other in providing comprehensive solutions to the various challenges faced by the global community. The integration of science and religion is not only relevant in addressing ethical and moral issues but also in building a holistic and inclusive education system. The Universitas Islam Negeri Sunan Kalijaga Yogyakarta is one of the institutions that have consistently developed the paradigm of integrating science and religion, known as the integrative-interconnective approach. This paradigm aims not only to unify these two disciplines but also to dynamically connect them within the realm of both theory and praxis in higher education. The paradigm serves as a model for the development of knowledge grounded in Islamic values while simultaneously opening a dialogue with modern science. However, the implementation of the integration of science and religion in the era of globalization faces various challenges, ranging from resistance to the paradigm shift, limited resources, to the pressure from the predominantly secular modernization. Nevertheless, significant opportunities have also emerged with the growing academic literature that elaborates on this approach, such as the journal Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies and other works highlighting the importance of renewing the scientific paradigm in Islamic higher education institutions